2006
DOI: 10.1159/000091498
|View full text |Cite
|
Sign up to set email alerts
|

Role of Latent Genital Tuberculosis in Repeated IVF Failure in the Indian Clinical Setting

Abstract: Genital tuberculosis is reported to be a major pelvic factor causing infertility in Indian women and often exists without any apparent signs and symptoms. The role of latent tuberculosis in repeated IVF failure in unexplained infertility is examined. 81 women with unexplained infertility having repeated IVF failure tested for Mycobacterium tuberculosis using PCR, ZN staining and BACTEC-460 culture were selected. Fresh IVF-ET or frozen embryo transfer (FET) was attempted on patients successfully treated with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 26 publications
1
46
1
Order By: Relevance
“…These women may have endometrial and tubal ciliary damage, which prevents a normal conception and implantation. Yet another reason for poor fertility is a diminished ovarian reserve because of GTB [19]. There is even a role for latent GTB in infertility because dormant mycobacteria present in the basal endometrium may impair the endometrial and subendometrial blood flow [19].…”
Section: Discussionmentioning
confidence: 99%
“…These women may have endometrial and tubal ciliary damage, which prevents a normal conception and implantation. Yet another reason for poor fertility is a diminished ovarian reserve because of GTB [19]. There is even a role for latent GTB in infertility because dormant mycobacteria present in the basal endometrium may impair the endometrial and subendometrial blood flow [19].…”
Section: Discussionmentioning
confidence: 99%
“…Jindal [11] observed IVF-ET to be most successful out of all ART modalities in genital TB patients with 17.3 % conception rate in contrast to only 4.3 % with fertility enhancing surgery. Dam et al [45] found latent genital TB responsible for repeated IVF failure in young Indian patients in Kolkata presenting with unexplained infertility with apparently normal pelvis and non-endometrial tubal factors. If after ATT their tubes are still damaged but their endometrium is receptive (no adhesions or mild adhesions which can be hysteroscopically resected), IVF-ET is recommended [8,46].…”
Section: In Vitro Fertilization (Ivf)mentioning
confidence: 99%
“…Genital tuberculosis (GTB) in women is an important clinical problem often associated with infertility (Bose 2011;Dam et al 2006). According to an estimate, 5 % of women seeking infertility treatment have GTB worldwide (Malik 2003).…”
Section: Introductionmentioning
confidence: 99%